Corticotropin, lipotropin, and beta-endorphin production by a human nonpituitary tumor in culture: evidence for a common precursor. - Bertagna, X Y (1978)
A continuous line (DMS-79) of human pulmonary small cell carcinoma cells was shown to secrete immunoreactive adrenocorticotropin (ACTH), lipotropin, and beta-endorphin concomitantly into the culture medium. Gel filtration of the culture medium demonstrated at least five components: high molecular weight material(s) that had ACTH, lipotropin, and beta-endorphin immunoreactivities and materials similar to ACTH, beta-lipotropin, gamma-lipotropin, and beta-endorphin in their immunoreactivities and apparent molecular weights. The same components were observed when gel filtration was carried out in 6 M guanidine-HCl, and the high molecular weight material(s) appeared to consist of more than one component, with molecular weights in the range of 15,000-40,000. Immune affinity chromatography of the high molecular weight component(s) from gel filtration with a specific anti-(1-24)ACTH serum demonstrated that the ACTH, lipotropin, and beta-endorphin immunoreactivities were possessed by the same molecule(s), suggesting that ACTH, lipotropins, and beta-endorphin were derived from a common, high molecular weight precursor.